À propos des investissements fixes des entreprises du modèle CANDIDE - Gaudet, Gérard; Rouzier, Philippe (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractThe purpose of this paper is to comment on the investment equations of the CANDIDE model. The formulation of these equations is based on Jorgenson's theory of investment which is frequently used as a basis for investment expenditures analysis.In the first two sections the authors endeavour to situate Jorgenson's model with respect to other approaches to investment theory. The last two sections contain, first, an evaluation of the way the Jorgenson's model has been adapted and, secondly, an evaluation of the problem of estimation and stability of the investment model.